Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1001/archpediatrics.2010.282
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile Infection in Hospitalized Children in the United States

Abstract: To evaluate the trend in Clostridium difficile infection (CDI) among hospitalized children in the United States and to evaluate the severity of and risk factors associated with these cases of CDI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
158
2
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(170 citation statements)
references
References 47 publications
5
158
2
5
Order By: Relevance
“…20 This method has previously been used in evaluating disease outcomes for other hospital-acquired infections. [21][22][23] VRE infection was the dependent variable, and demographic variables, hospital/ geographic variables, and 389 of the most common comorbid diagnostic and procedure CCS codes, as discussed previously, were the independent variables in the model. Patients with an indication of VRE infection (cases) were matched by high-dimensional propensity score, using a greedy matching algorithm, to patients who did not have VRE (controls), with a 1-to-5 matching ratio.…”
Section: Discussionmentioning
confidence: 99%
“…20 This method has previously been used in evaluating disease outcomes for other hospital-acquired infections. [21][22][23] VRE infection was the dependent variable, and demographic variables, hospital/ geographic variables, and 389 of the most common comorbid diagnostic and procedure CCS codes, as discussed previously, were the independent variables in the model. Patients with an indication of VRE infection (cases) were matched by high-dimensional propensity score, using a greedy matching algorithm, to patients who did not have VRE (controls), with a 1-to-5 matching ratio.…”
Section: Discussionmentioning
confidence: 99%
“…1 Nylund et al evaluated data from 1997, 2000, 2003, and 2006 and demonstrated an increase in the number of CDIs, from 3565 cases in 1997 to 7779 cases in 2006 (total cases, 21 274; P < .01). 2 Zilberberg et al also demonstrated an increase of hospitalizations attributable to C difficile, from 7.24 to 12.80/10 000 hospitalizations. 3 The emergence of the epidemic strain of toxin-producing C difficile (North American pulsed field type 1 [NAP1]) in recent years may have changed the epidemiology in children.…”
Section: Introductionmentioning
confidence: 91%
“…[1][2][3] Kim et al evaluated the annual incidence of C difficile-associated disease from 2001 to 2006 at 22 freestanding children' s hospitals and found increases in the number of admissions (2.4 to 4.0/1000 admissions; P = .04) as well as the number of cases per patient-days in the hospital (4.4 to 6.5 cases/10 000 patient-days; P = .06). 1 Nylund et al evaluated data from 1997, 2000, 2003, and 2006 and demonstrated an increase in the number of CDIs, from 3565 cases in 1997 to 7779 cases in 2006 (total cases, 21 274; P < .01).…”
Section: Introductionmentioning
confidence: 99%
“…Even if the burden of disease regards the adult age, a concomitant increase of number of hospitalizations, hospital length of stay, medical expenses, colectomy rate for CDI have been reported also in children [8,9]. In spite of this phenomenon, CDI infection is rarely severe at this age, and severity is strongly related to the presence of multiple antibiotic courses [4].…”
Section: Exploding or Rare Disease?mentioning
confidence: 99%
“…Of interest, both hospital (HA) -and community (CA) -associated CDI are increasing [9], but while in HA-CDI the above mentioned risk factors are usually found, these factors are often lacking in CA-CDI [10], where the main determinant factor is the presence of comorbidities and among these of inflammatory bowel disease (IBD) [6][7][8][9].…”
Section: Exploding or Rare Disease?mentioning
confidence: 99%